CELEBRITY ENDORSEMENT AND ITS IMPACT ON MARKETING PERFORMANCE: AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF MANAGERS AT ASIACELL COMPANY – IRAQ (World Economics and Finance Bulletin, 2025)
This research aims to examine the impact of celebrity endorsement on the marketing performance of Asiacell Telecommunications Company in Iraq. The research problem lies in Asiacell's inability to achieve the desired level of marketing performance compared to telecommunications companies at both regional and global levels. Although celebrity endorsement is considered an innovative marketing strategy, its direct impact on the company’s marketing performance has not been sufficiently studied in the Iraqi market. Therefore, this research seeks to fill that gap and provide scientific insights that support the development of marketing strategies and enhance the company’s competitive position
Keywords: Celebrity endorsement; Marketing performance; Asiacell Telecommunications Company in Iraq